A novel intracranial exchange guidewire improves the navigation of various endovascular devices: An in vitro study of challenging situations. Issue 5 (October 2022) - Kaneko, Naoki; Takayanagi, Ariel; Saber, Hamidreza; Guo, Lea; Tateshima, Satoshi
Objective: Neuroendovascular procedures rely on successful navigation and stable access to the target vessel. The Stabilizer is a 300 cm long exchange wire with a 0.014 diameter and a soft, flexible stent at the distal end designed to assist with navigation and device delivery. This study aims to assess the efficacy of the Stabilizer for navigation in a variety of challenging environments. Methods: The efficacy of the Stabilizer was evaluated using three challenging vascular models: a giant aneurysm model, a severe tortuosity model, and an M1 stenosis model. The Stabilizer was compared with a conventional wire during navigation in each model. Results: In the giant aneurysm model, there was no significant difference of success during straightening of a looped wire and significantly higher success rates when advancing an intermediate catheter with the Stabilizer beyond the aneurysm neck compared to a conventional guidewire. The Stabilizer also significantly increased success rates when advancing an intermediate catheter through a model with severe tortuosity compared to a conventional guidewire, as well as exchange maneuver for intracranial stenting in a stenosis model compared to an exchange wire. Conclusions: In our experimental model, the Stabilizer significantly improved navigation and device delivery in a variety of challenging settings compared to conventional wires.